Cooperação para inovação nas universidades: uma abordagem por meio da inovação aberta - Marques, Humberto Rodrigues (2017)
The present dissertation, which has been organized in the form of scientific articles, aims at the process of open innovation that is occurring in the universities. Specifically, the overall objective has been divided them into three specific objectives, namely: a) to analyze in the literature of how the open innovation approach is being applied in the context of universities; b) to identify the main actors that the universities relate in the exchange of knowledge for the generation of technology; and c) to verify if there are groups of teachers that present different positions regarding the cooperation between university and its main agent of partnership, the companies, as well as the factors that discriminate these groups. In the second part of the dissertation are presented the three articles developed based on the specific objectives defined. In the first article a systematic review of literature is carried out, apprehending what has been discussed about the subject of open innovation in universities. In the bibliometric analysis, it was verified that the approach of open innovation in universities is recent and with less intensity, with an increase in the last years, not being identified neither authors nor magazines and events that possessed large amounts of publications on the subject. Regarding the integrative findings, we did not identify expressive cooperation of universities with external entities, focusing only on the relationship with industry, which still little occur due to several types of barriers. The second article had as objective to identify the main partnerships of the universities regarding the cooperation in the technological development, analyzing the patents deposited by the federal universities of Minas Gerais. It was verified that there was a growth in the number of patent deposits with co-titration per year until 2012, with a subsequent decline, where it was found that public institutions, especially educational institutions, are the major partners of the federal universities of Minas Gerais. Also, it was verified that the deposits have concentration in two areas of knowledge: "human needs" and "chemistry or metallurgy". Finally, in the third article we aimed to verify if there are groups of professors of federal university from Minas Gerais that stand in a different way regarding the cooperation between university and its main agent of partnership, the companies, as well as the factors that discriminate these groups. Through cluster analysis and discriminant analysis, we identified two groups of teachers, where Cluster 1 is made up of teachers with higher degree of qualification and more academics who have already cooperated with companies and Cluster 2 is made up of teachers with lower degree of qualification and that cooperated less with companies, so that these groups agreed differently with 7 factors of university-company cooperation. In this way, in general, the present research debates the universe of universities that are increasingly adhering to a more entrepreneurial mission, as well as opening their environment of innovation, to know the peculiarities of this relationship.